Sistem Pendukung Keputusan Untuk Menentukan Kualitas Kopi Berbasis Analytical Heirarchy Process Di Pekon Batukeramat - Samsudin Samsudin; Emilia Jaya; Megawati Asyari (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2018)
Determination of the quality of coffe beans besicallly requires expertisme and checks against that coffee beans. That require time not a bit in determya.the criteria for determining the quality of the previous coffee beans have been set in the international scale in determining the quality of coffee beans on the national selec of each agency. Has its owen criteria in determining the quality of coffee beans that also previously referred to the criteria determination of intentional quality of coffee beans. As one of the existing plantations in Indonesia coffee plantation. The village of sacred stone certainly uses the determination of quality in producing coffee beans.where the criteria are. In use is the value of moisture content, the defect value of the seed,and the height of land where coffee is planted. With determination of the Arabica coffee beans with water content criteria, defects of seeds and altitude of and on coffee plantations in the village of sacred stone ,in this study using AHP method. Where the AHP method can produce the output of the calculation based on the input and the wight value can be adjusted with research criteria that will be applied. The result of the research is the apication the can determine the quality of coffee beans with the input of water Content, seed defects andatitude of land using AHP method.(analytical hierarchy process)